Frontier and developing Asia the next generation of emerging markets - Schipke, Alfred 1959-; International Monetary Fund (Washington, DC International Monetary Fund, 2015)
Frontier economies are receiving increasing attention from policymakers, investors, and academics. Compared with other low-income countries they have experienced rapid growth over the last two decades, giving rise to speculation as to whether they will become the next generation of emerging markets. This book looks at the growing importance of the countries that make up frontier and developing Asia from different angles, including achieving inclusive growth, financial sector deepening, and strengthening policy frameworks.
The growing importance of frontier and developing Asia / Alfred Schipke. -- Lessons for frontier economies from the recent experience of emerging markets / Sunil Sharma. -- Diversification, growth, and volatility / Ke Wang. -- Growth slowdown: are frontier and developing Asian countries different? / Damien Puy. -- Achieving inclusive growth / Murtaza Syed. -- Financial sector deepening and transformation / Marco Arena. -- Addressing financial sector vulnerabilities / Xuan Tu. -- Frontier markets in Asia and beyond / Chris Walker. -- Monetary policy frameworks: an assessment / Alexandra Peter.
Includes bibliographical references and index.
Keywords: Economic development -- Asia -- 21st century; Asia -- Economic conditions -- 21st century